A ADOÇÃO DE CRIANÇAS POR CASAIS LBGTQIA+ EM BETIM/MG: UMA COMPARAÇÃO ENTRE DADOS MUNICIPAIS E CONVENÇÕES INTERNACIONAIS - MACIEL DINIZ BERNARDES, ANA LAURA; DE PAULA MATOS, BRENDA; CAMPOS GOMES, MARIANA ELIS; DAIANE DOS SANTOS ALVES, GARDÊNIA; BARBOSA MADUREIRA, KAROLLAYNE; DOS SANTOS CAMARGOS , LORENA; DIAS DE MELO, LETÍCIA GABRIELA; MARTINS OLIVEIRA, MARIA VITÓRIA; VITOR MARTINS SILVA, THAYNÁ; DE MENDONÇA GONÇALVES LEITE, MATHEUS (Sinapse Múltipla, 2019)